(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Graphene-modified layer is obtained on 5083 aluminum alloy sheet material via friction stir processing. A special groove is cut in the aluminum plate and filled with graphene. The processing is carried out using an innovative technology with an appropriate tool. The temperature at a chosen point in the heat affected zone is measured in real-time by a remote-control system. Test specimens were prepared from the processed plates and metallographic analysis was carried out. The microhardness of the modified layer is measured perpendicular to the direction of processing and in depth. An increase in microhardness relative to that of the base material is found.